Balé-Balé: “Archetype” Arsitektur Tradisional Bali Aga Di Desa Pengotan (Balé-Balé: “Archetype” Of Bali Aga Traditional Architecture At Pengotan Village) - Himasari Hanan (Tesa Arsitektur, 2017)
Abstract: Bali Aga traditional settlements at Pengotan village, on one hand, exhibits variety of architectural expression, but at the other hand, reveals uniformity in ordering space and house form. All traditional houses in earlier phase are uniform because they are erected according to standardized building customs. Availability of cheaper new building materials and practical construction methods have induced Pengotan people to renovate their traditional houses in present architectural style. This research is to investigate the changing process of house form and to which extent these changes have modified traditional building system. Do inhabitants tend to preserve traditional style or adopt recent architecture. The investigation has indicated that traditional bamboo benches are key preconception of space and form design in Bali Aga traditional houses. Layout system of benches inside and outside the house persisted even though the house has endured renovation. Along the way, the tradition of putting bamboo benches in front the house has induced the concept of verandah in the house. Since traditional houses are placed uniformly in a row, the new verandah has created a long open space for leisure and common activities where people have a free visual and audial access to neighbours. Keywords: balé-balé; Bali Aga; traditional architecture; interactive social space; verandah Abstrak: Arsitektur rumah tradisional Bali Aga di Pengotan berkaitan erat dengan sumber daya alam di sekitarnya dan pola kegiatan penghuni yang dipengaruhi oleh pandangan hidupnya. Permukiman tradisional Bali Aga di desa Pengotan pada satu sisi memperlihatkan keragaman arsitektur, namun pada sisi yang lain memperlihatkan konsistensi dalam tata atur ruang dan bentuk bangunan. Semua rumah, pada awalnya, dibangun dengan mengikuti ketentuan adat sehingga arsitektur semua bangunan adalah seragam. Adanya bahan bangunan baru dan teknologi membangun yang lebih mudah dan murah mendorong orang untuk merenovasi bangunan yang mulai lapuk. Penelitian ini mengkaji bagaimana perubahan bentuk rumah berlangsung, serta bagian mana dari bangunan yang cenderung tetap dan mana yang berubah. Selain itu, pertanyaan penelitian adalah apakah perubahan ini memberikan dampak bagi keberlanjutan rumah tradisional. Hasil penelitian menunjukkan bahwa balé-balé bambu merupakan komponen bangunan yang menentukan susunan ruang dan bentuk bangunan. Konsep penempatan balé-balé bambu dalam bangunan tidak pernah mengalami perubahan walaupun rumahnya menjadi berubah karena direnovasi. Dalam proses renovasi konsep balé-balé bambu melahirkan konsep ruang yang baru, yaitu ruang teras di depan rumah. Keberadaan ruang teras ini menjadikan halaman rumah sebagai ruang sosial yang interaktif dan produktif. Kata kunci: balé-balé; Bali Aga; arsitektur tradisional; ruang interaksi sosial; ruang teras